Empretec : the first ten years : empowering entrepreneurs for the 21 st century (UN GenevaCH, 1999)
Reviews the Empretec concept and how it evolved over the past 10 years and discusses its relevance for the next decade. Describes the programme approach, Empretec's assistance to entrepreneurs, the service structure, the insitutional set-up and the international networking mechanisms.
Keywords: ENTREPRENEURSHIP